2021
DOI: 10.1111/jcal.12551
|View full text |Cite
|
Sign up to set email alerts
|

The structure of student engagement in online learning: A bi‐factor exploratory structural equation modelling approach

Abstract: Enhancing student engagement plays a critical role in reducing student drop‐out rate in online learning as students usually feel isolated and disconnected in this learning environment. This requires a clear conceptualization of the student engagement construct and its underlying structure. However, the conceptual understanding of the student engagement construct has long been impeded by the inconsistency in its multidimensional structure and the conceptual ambiguity among its components. This study aims to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…Such activities with technological tools may lead to issues with ethical and moral values associated with the use of digital technology. It was found that technology can transform interest and feelings, increase happiness and reduce boredom, sadness, and anxiety indicating that technology adoption in virtual learning may have a positive impact on the emotional engagement [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such activities with technological tools may lead to issues with ethical and moral values associated with the use of digital technology. It was found that technology can transform interest and feelings, increase happiness and reduce boredom, sadness, and anxiety indicating that technology adoption in virtual learning may have a positive impact on the emotional engagement [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various competing and contrasting ideas about students’ engagement in an online environment [ 44 ]. For example, Bowden et al [ 45 ] proposed four pillars of student engagement: affective, social, cognitive, and behavioral ( Fig 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second domain of motivation and emotion includes the constructs academic motivation (Litalien et al, 2017 ; Guay and Bureau, 2018 ; Gordeeva et al, 2020 ; Howard et al, 2020 ; Kartal, 2020 ; Guay et al, 2021 ; Dierendonck et al, 2022 ), sport motivation (Appleton et al, 2016 ; Milton et al, 2018 ; Stenling et al, 2018 ; Cece et al, 2019 ; Méndez-Giménez et al, 2020 ; Rodrigues et al, 2020 ), work motivation (Burk and Wiese, 2018 ; Calkins, 2018 ; Howard et al, 2018 , 2020 , 2021 ; Gegenfurtner and Quesada-Pallarès, 2022 ), job satisfaction (Sutherland, 2020 ), affective commitment (Perreira et al, 2018 ), work engagement (Gillet et al, 2019 ; Huyghebaert-Zouaghi et al, 2021a , 2022 ), teacher engagement (Perera et al, 2018b ), student engagement (Hoi and Hang, 2021 ; Dierendonck et al, 2022 ; Tomás et al, 2022 ), basic psychological needs (Stenling et al, 2015 ; Sánchez-Oliva et al, 2017 ; Tóth-Király et al, 2018 , 2019 ; Bhavsar et al, 2019 , 2020 ; Garn et al, 2019 ; Burgueño et al, 2020a , b ; Cromhout, 2020 ; Gillet et al, 2020 ; Gucciardi et al, 2020 ; Huyghebaert-Zouaghi et al, 2021b ; Rodrigues et al, 2021 ), subjective task value (Fadda et al, 2020b ; Part et al, 2020 ), flow (Kyriazos et al, 2018b ; Gu et al, 2020 ), interest (Garn, 2017 ), locus of causality (Howard et al, 2020 ), attitudes (Deemer et al, 2014 ), purpose (Summers and Falco, 2020 ), self-efficacy (Barbaranelli et al, 2018 ; Dominguez-Lara et al,…”
Section: Resultsmentioning
confidence: 99%